Changes in traffic accident risk degree according to driving workload rate and moderate effect of ego-resilience - Song, HunHwa; Lee, SoonChul (Korean Journal of Industrial and Organizational Psychology, 2011)
This research was conducted to verify changes in traffic accident risk level according to driving workload rate and the moderate effect of ego-resilience. Several hypotheses were made by considering previous studies, in which the traffic accident risk level measured according to Traffic Accident Risk Index (TARI) and Driving Behavior Determinants (DBD) differed from the driving workload rate. Furthermore, Ego-resilience was also considered as a human factor, which has the moderate effect between workload and TARI, DBD. A total of 260 drivers participated in the survey. The result of the factor analysis revealed that the DBD questionnaire could be divided into five factors (i.e., Impatient Driving, Situational Inadaptability, Distracted Driving, Drunken Driving, and Speed Driving). In order to verify changes in those behaviors according to driving workload rate, variation analysis was conducted. The results revealed that Impatient Driving, Situational Inadaptability, and Distracted Driving had significant relationships with driving workload rate. Moreover, the moderate effect of Ego-resilience related to Situational Inadaptability was verified by hierarchical regression analysis. We expect that the result of this study could be used to develop countermeasures to excessive driving workload.